On the importance of speed skating and fitness in short track speed skating - Thibault, J. (1999)
The object of this article is to investigate the importance of speed and fitness in the outcome of a short track speed skating competition. METHOD The Canadian and United States National Trials results over the past 3 years were collected and compared to the pursuit results. A Spearman correlation was then performed to establish the relationship between the two results. A correlation coefficient is an indicator of the relationship between two variables. If a relationship between two variables is perfect, i.e. if a fluctuation in the value of one of them brings an equal change in the other one, the correlation coefficient will be 1. If no relation is found between the variables then the coefficient is 0. RESULTS AND INTERPRETATION A correlation of .90 between the results of the pursuit and the final result of the trials indicates a strong relationship between these two variables. In simple terms, a change in the position of a skater after the pursuit will bring, in general, an equal change to the overall results of the trials. This observations suggests that speed and fitness, the two key elements of the pursuit, are more important than previously thought in the final results of a short track competition. If the fastest skater of the pursuit has a good probability (81%) to be the best skater or 5h3 overall trials (correlation .90), then the importance of strategy and tactics is far less than the importance of speed and fitness. These results, in my opinion, could have shown an even higher correlation if we had taken into consideration that many athletes competed only in part of the overall trials due to the injury or withdrawal during the competition. PRACTICAL IMPLICATIONS Statistical analysis is not, of course, perfect. It shows us the general tendency of the results observed. For example, I did not find one instance where the 16-place qualifier of the pursuit won the overall team trials but it does not mean that this is impossible to achieve. The correlations presented above put a lot of importance on speed and fitness. Speed is mainly developed through technique and strength while fitness will be dependant on the training plan leading to the trials. It could also be argued that racing experience could be less important than previously though. Opportunities for racing have always been a major concern for coaches and athletes, although necessary, it is possible that the training environment of a club (Centre) could be organized to maximize racing experience.